2011
DOI: 10.1111/j.1349-7006.2011.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen suppresses proliferation of castration‐resistant LNCaP 104‐R2 prostate cancer cells through androgen receptor, Skp2, and c‐Myc

Abstract: Summary Androgen ablation therapy is the primary treatment for metastatic prostate cancer. However, this therapy is associated with several undesired side-effects, including increased risk of cardiovascular diseases. To study if termination of long-term androgen ablation and restoring testosterone level may suppress the growth of relapsed hormone-refractory prostate tumors, we implanted testosterone pellets in castrated nude mice carrying androgen receptor (AR)-positive LNCaP 104-R2 cells, which relapsed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 39 publications
3
99
0
Order By: Relevance
“…Furthermore, the simultaneous knockdown of p62 and AR suppressed hypoxia-induced apoptosis. This pro-apoptotic action of higher AR levels is consistent with studies demonstrating that overexpression of AR suppresses cell proliferation in AR-negative PC3 and LNCaP 104-R2 [40,41]. Chronic hypoxia induces resistance to apoptosis in LNCaP cells [42,43], and hypoxia-induced autophagy promotes tumor cell survival and chemoresistance in hepatocellular carcinoma, glioblastoma, and prostate cancer [44][45][46].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the simultaneous knockdown of p62 and AR suppressed hypoxia-induced apoptosis. This pro-apoptotic action of higher AR levels is consistent with studies demonstrating that overexpression of AR suppresses cell proliferation in AR-negative PC3 and LNCaP 104-R2 [40,41]. Chronic hypoxia induces resistance to apoptosis in LNCaP cells [42,43], and hypoxia-induced autophagy promotes tumor cell survival and chemoresistance in hepatocellular carcinoma, glioblastoma, and prostate cancer [44][45][46].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, it has been suggested that the androgen-activated AR acts also as a tumor suppressor for prostate cancer [9]. In line with this, treatment of mice with SAL inhibits the growth of human CRPCa cells in xenograft mouse model system in vivo [39, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of Skp2 in vivo triggers cellular senescence via up-regulation of p21 Cip1 , p27 Kip1 , and ATF4, therefore suppresses the development of PCa [60]. Skp2 was reported to cross-talk with PI3K/Akt [61], AR [62], PTEN [55], and BRCA2 [63] signaling pathways in PCa cells. As a result, Skp2 plays essential role in the development and progression of human PCa [49].…”
Section: Discussionmentioning
confidence: 99%
“…Relative cell number was analyzed by measuring the DNA content of cell lysates with the fluorescent dye Hoechst 33258 (Sigma, St. Louis, MO, USA) as described previously [18, 19, 26, 62]. All readouts were normalized to the average of the control condition in each individual experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation